THE FORMATION OF A CULTURE OF READING AS A FACTOR OF INCREASING THE MORALE OF YOUNG PEOPLE - Kuchkarova Aisha Oltibayevna (Journals Park Publishing, 2022)
In this article, the issue of educating the culture of reading in the formation of the spirituality of young people is raised, and the work carried out by the state in this regard and the practical work on their implementation are analyzed.
Keywords: book; reading culture; spirituality